The Warburg Effect as a Type B Lactic Acidosis in a Patient With Acute Myeloid Leukemia: A Diagnostic Challenge for Clinicians - Brault, Clément; Zerbib, Yoann; Delette, Caroline; Marc, Julien; Gruson, Bérengère; Marolleau, Jean P.; Maizel, Julien (Frontiers in Oncology, 2018)
Introduction: The Warburg effect (WE) is an uncommon cause of type B lactic acidosis (LA) due to a deregulation of carbohydrate metabolism in neoplastic cells where lactic fermentation predominates over oxidative phosphorylation regardless of the oxygen level. Case presentation: We report the case of a 57-year-old man presenting with concomitant acute myeloid leukemia and type B LA with asymptomatic hypoglycemia. We did not find arguments for a septic state, liver dysfunction, or acute mesenteric ischemia. The Warburg effect was suspected, and chemotherapy was immediately undertaken. We observed a rapid and sustained decrease in lactate level and normalization of blood glucose. Unfortunately, we noted a relapse of acute leukemia associated with WE soon after treatment initiation and the patient died in the Intensive Care unit. Discussion: Some patients may present complications directly related to an underlying hematological malignancy. The Warburg effect is one of these complications and should be suspected in patients with both hypoglycemia and LA. We propose a checklist in order to help clinicians manage this life-threatening complication. Before considering WE, clinicians should eliminate diagnoses such as septic shock or mesenteric ischemia, which require urgent and specific management. Conclusion: The diagnosis of WE can be challenging for clinicians in the Hematology department and the Intensive Care unit. Prompt diagnosis and rapid, adapted chemotherapy initiation may benefit patient survival.